Implementasi Peraturan Daerah Kabupaten Pangandaran Nomor 5 Tahun 2015 Tentang Pengelolaan Zakat, Infaq, Shodaqoh Untuk Penanggulangan Kemiskinan Di Kabupaten Pangandaran - Iwan Iswanto (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to find out how far the implementation of the Pangandaran Regency Regional Regulation Number 5 of 2015 concerning the Management of Zakat, Infaq and Shodaqoh for Poverty Alleviation in Pangandaran Regency, what are the obstacles and to find out what efforts have been made by the Pangandaran Regency National Amil Zakat Agency to overcome these obstacles . The Pangandaran Regency National Amil Zakat Agency, hereinafter referred to as Regency BAZNAS, is an institution that carries out national zakat management in Pangandaran Regency. BAZNAS Pangandaran Regency is a Zakat Management organization formed by the Government with the task of collecting, distributing and utilizing zakat in accordance with Islamic religious provisions and applicable laws and regulations. In this study the method used was a qualitative approach with data collection techniques using observation and interviews. From the results of the research and discussion, it shows that the implementation of the Regional Regulation of Pangandaran Regency Number 5 of 2015 concerning Management of Zakat, Infaq and Shodaqoh for Poverty Alleviation in Pangandaran Regency has not been carried out properly. This is evidenced by the lack of effective communication between the BAZNAS of Pangandaran Regency and the Regional Head as a political position as well as the regional Secretariat whose job is to assist regional heads in formulating policies and coordinating regional offices and regional technical institutions. The absence of strict sanctions from the regional head to civil servants who do not comply with these regulations has hindered poverty alleviation from Zakat, Infaq and Shodaqoh funds collected by BAZNAS. Zakat, Infaq and Shodaqoh carried out by BAZNAS did not reach the target, as a result the assistance distributed by BAZNAS tended to be consumptive funds with little value. Lack of quality and quantity of Human Resources for BAZNAS Pangandaran Regency, so when the aid funds were channeled for business capital assistance, BAZNAS Pangandaran Regency did not provide assistance and utilization of beneficiaries, so that the funds received were ultimately not optimal for poverty alleviation, and led to when the business capital runs out, in the end the business closes.